Karakteristik Siswa Program Tahfidz dalam Proses Menghafal di SMA Al-Muhajirin Purwakarta ditinjau dari Tipologi Kepribadian Hippocrates-Galenus - Sani, Lutfiah; Munastiwi , Erni (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2022)
This study identifies and describes the characteristics of the Tahfidz program students in the process of memorizing the Qur'an at Al-Muhajirin High School Purwakarta as one of the educational institutions that has the Tahfidz Al-Qur'an program for class X-XI students located in the Citapen area of ​​Purwakarta. West Java. Researchers formulate problems related to personality types and student characteristics in the process of memorizing the Qur'an in terms of the Hippocrates-Galenus personality typology. The approach used is descriptive qualitative with test and interview methods. Based on the results of the study, it was identified that the students of the Tahfidz program at SMA Al-Muhajirin Purwakarta had 4 mixed personality types including a natural mixture, namely Melancholy-Phlegmatic, complementary mixture, namely Sanguine-Phlegmatic and Melancholy-Choleric, and the opposite mixture, namely Choleric-Phlegmatic. Characteristics of Tahfidz program students in the process of memorizing the Qur'an regarding the motivation and methods used to memorize the Qur'an in terms of the Hippocrates-Galenus personality typology.